Study the heat dissipation performance of lithium‐ion battery liquid cooling system based on flat heat pipe. (24th March 2021) - Hu, Hao; Xu, Xiaoming; Li, Renzheng; Yuan, Qiuqi; Fu, Jiaqi
Summary: This paper improves the thermal management system of lithium‐ion battery through the high thermal conductivity flat heat pipe, and attempts to improve its performance. The adoption of flat heat pipes reduces the problem of poor heat dissipation in the direction of the coolant flow when the liquid cooling plate is used alone, and increases the heat conduction in the longitudinal direction of the battery. A three‐dimensional simulation model is established to study the influence of the number and width of flat heat pipes on the maximum temperature rise and temperature difference of lithium‐ion batteries at a certain discharge rate. It is found that after adding flat heat pipes, the maximum temperature rise and temperature difference of the battery decreased. The heat dissipation performance reaches the best when the flat heat pipe number is 11 and the maximum temperature difference can be controlled below 5°C at 3 C discharge rate with 11 flat heat pipes.